2021
DOI: 10.3390/nu13092975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Postbiotic and Prebiotic Mixture on Suckling Rats’ Microbiota and Immunity

Abstract: Human milk serves as a model for infant formula providing nutritional solutions for infants not able to receive enough mother’s milk. Infant formulas aim to mimic the composition and functionality of human milk by providing ingredients reflecting those of the latest human milk insights, such as prebiotics, probiotics and postbiotics. The aim of this study was to examine the effects of the supplementation with a postbiotic (LactofidusTM) and its combination with the prebiotics short-chain galactooligosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 100 publications
(171 reference statements)
5
15
1
Order By: Relevance
“…The postbiotic increased the levels of MUC2 whereas scGOS/lcFOS, combined or not with Lactofidus TM , induced the expression of MUC3. These effects in the infection context on the expression of MUC genes agree with those found in a healthy model of suckling rats [ 23 ]. We also observed that scGOS/lcFOS reduced the levels of MUC2 in 8-day-old suckling rats [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The postbiotic increased the levels of MUC2 whereas scGOS/lcFOS, combined or not with Lactofidus TM , induced the expression of MUC3. These effects in the infection context on the expression of MUC genes agree with those found in a healthy model of suckling rats [ 23 ]. We also observed that scGOS/lcFOS reduced the levels of MUC2 in 8-day-old suckling rats [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the REF group constituted the non-infected non-supplemented control group. The selection of the product doses was based on previous works [ 13 , 23 , 27 , 32 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations